Malo kingi: A new species of Irukandji jellyfish (Cnidaria: Cubozoa: Carybdeida), possibly lethal to humans, from Queensland, Australia - Gershwin, Lisa-Ann (Zootaxa, 2007)
Irukandji stings may be lethal to humans, and yet, until late 2005, only one of the many suspected Irukandji stingers had been formally named and classified. This paper describes Malo kingi, n. sp., which is apparently responsible for a recent fatality. This species differs from all other cubozoans in having halo-like rings of tissue encircling the tentacles, with club-shaped Type 4 microbasic mastigophores inserted end-on around the periphery of the rings. It further differs from its only current congener, Malo maxima, in having: a much smaller, more rounded body; different tubule winding patterns in the undischarged nematocysts; spines confined to the distal-most portion of the shaft in the discharged nematocysts; relatively broader pedalia; somewhat less well defined rhopalial horns; and perradial lappets with a greater number of nematocyst warts and nipple-like terminal extensions. Much additional work is needed to better understand the general biology of this and other dangerous species so as to prevent further fatalities, debilitating illnesses, and threats to the tourism industry resulting from the marine stinger problem. Treatment of envenomations, management issues regarding sting prevention, and the related implications for tourism, all rely on being able to consistently and accurately identify public health hazards. The need still exists for an aggressive awareness campaign aimed at residents and visitors regarding education and prevention of Irukandji stings.